2014
DOI: 10.1016/j.bjid.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic study documents divergence in the pathogenesis of bloodstream infection related central venous catheters in neonates

Abstract: The majority of infections caused by S. epidermidis in neonates had an unknown origin, although 33.3% appeared to have been acquired intraluminally and extraluminally. We observed a polyclonal profile between sensitive samples and a prevalent clone (A) between resistant samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
2
0
8
Order By: Relevance
“…Our results which showed that S . epidermidis constituted 81.7% of CoNS species is consistent with this notion and was similar to the results of previous studies in Norway [ 15 ], Brazil [ 38 ] and Turkey [ 39 ] where S . epidermidis was reported as the most common CoNS species associated with neonatal bloodstream infections.…”
Section: Discussionsupporting
confidence: 93%
“…Our results which showed that S . epidermidis constituted 81.7% of CoNS species is consistent with this notion and was similar to the results of previous studies in Norway [ 15 ], Brazil [ 38 ] and Turkey [ 39 ] where S . epidermidis was reported as the most common CoNS species associated with neonatal bloodstream infections.…”
Section: Discussionsupporting
confidence: 93%
“…Tests were performed to determine the limit of detection of PCR using serial dilutions of genomic DNA, extracted from 10 3 colony-forming units per milliliter (CFU/ml) culture aliquots, plated on brain heart infusion (BHI) agar plates, to reproduce the minimum detectable level of CFUs 9 . In order to determine the sensitivity of the primer to lower DNA concentrations extracted from 10 3 CFU/ml, serial dilutions were prepared, and PCR was performed on the titrations using the same bacterial detection parameters.…”
mentioning
confidence: 99%
“…Bloodstream infection (BSI) remains the most frequent adverse event among premature infants worldwide, associated with increased hospital stay length and costs, poor outcomes, and even death. 1,2 The association of these infections with the use of central venous catheters (CVCs) in newborns ranges from 17.3/1,000 CVC-day in neonates weighing from 1,501 g to 2,500 g to 34.9/ 1,000 CVC-day in neonates <1,000 g. 3 Although the pathogenesis of catheter-related bloodstream infections (CR-BSIs) is multifactorial and complex, references from studies in adults indicate two main potential routes of contamination of the catheter tip: (1) extraluminal, that is, organisms present in patient skin at the insertion site can migrate into the catheter tract, resulting in colonization of the catheter tip-regarding short-term catheters, this is the most common source of infection; 4,5 and, (2) intraluminal, that is, after the first week of placement, intraluminal contamination and colonization after hub manipulation occurs, which is responsible for most CR-BSI. 6,7 In premature neonates, microbial translocation through the colonized mucosa is an underestimated source of infection that requires investigation.…”
Section: Introductionmentioning
confidence: 99%